Bimbingan Karier Dalam Media Portofolio Karier - Nida’u Diana; M. Ramli; Muslihati Muslihati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: Development of a career portfolio guide for students of senior high school  Bayt Al-Hikmah is a guide to career guidance activities that explore students' self-understanding in documenting and administering student learning outcomes in the form of career portfolios. Purpose of this research is to produce guidelines for students' career portfolios that are acceptable, in terms of accuracy, usability, convenience, and attractiveness. The design of the development uses the modified Borg and Gall (1983) R&D model. Data collection uses product assessment instruments by BK experts and media experts analyzed using inter-rater agreement techniques, with high index results in product acceptance in terms of accuracy, usability, convenience, and interest.Abstrak: Pengembangan panduan portofolio karier bagi siswa SMA Bayt Al-Hikmah adalah panduan kegiatan bimbingan karier yang menggali pemahaman diri siswa dalam mendokumentasikan dan mengadministrasikan hasil rekam jejak belajar siswa dalam bentuk portofolio karier. Tujuan penelitin ini adalah menghasilkan panduan portofolio karier siswa yang berterima, dari segi ketepatan, kegunaan, kemudahan, dan kemenarikan. Rancangan pengembangan menggunakan model R&D Borg and Gall yang dimodifikasi. Pengumpulan data menggunakan instrumen penilaian produk oleh Ahli BK dan ahli media yang dianalisis menggunakan teknik inter-rater agreement, dengan hasil indeks tinggi dalam keberterimaan produk pada hal ketepatan, kegunaan, kemudahan, dan kemenarikan.